2009
DOI: 10.1111/j.1468-232x.2009.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Injured Workers’ Underreporting in the Health Care Industry: An Analysis Using Quantitative, Qualitative, and Observational Data

Abstract: Underreporting of occupational injuries was examined in four health care facilities using quantitative, qualitative, and observational data. Occupational Safety and Health Administration logs accounted for only one-third of the workers' compensation records; 45 percent of injured workers followed by survey had workers' compensation claims. Workers reported 63 percent of serious occupational injuries. Underreporting is explained by time pressure and workers' doubts about eligibility, reputation, income loss, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…Analyses of continued under-reporting of occupational injuries have often included questions about possible economic and social penalties for workers who report occupational injuries 14 15. Findings in the present paper indicate a need for occupational health professionals to seriously evaluate the possibility of such penalties.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Analyses of continued under-reporting of occupational injuries have often included questions about possible economic and social penalties for workers who report occupational injuries 14 15. Findings in the present paper indicate a need for occupational health professionals to seriously evaluate the possibility of such penalties.…”
Section: Discussionmentioning
confidence: 78%
“…Although frequently used in occupational health studies, workers’ compensation databases are particularly vulnerable to under-reporting of occupational injuries. Galizzi et al 15 found that healthcare workers reported about 63% of reportable occupational injuries observed by researchers, whereas the workers’ compensation database captured about one-third of these injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Among nursing staff, documented injury rates have been reported at rates of 12.89 per 100 full-time employees, and this rate may be nearly double for nursing aides. 11 Beyond documented workplace injuries, which may be underreported, 12 self-reported musculoskeletal pain and symptoms (musculoskeletal disorders, or MSDs) is widespread among healthcare workers. 13-15 The one (1) -year prevalence rate of lower back pain in nursing personnel has been reported at over 60%.…”
Section: Introductionmentioning
confidence: 99%
“…One form of voice is expressing a concern or a complaint to a supervisor, employer, or regulatory body. There is significant evidence that workers often refrain from such action (Galizzi, Miesmaa, Punnett, & Slatin, 2010;Milliken, Morrison, & Hewlin, 2003;Morrison & Milliken, 2000;Salin, Teniälä, Roberge, & Berdahl, 2014) due, in part, to fear of consequences for speaking out. Gullone (2000) asserts fear is a normal reaction to real or imagined threats.…”
Section: Voice Silence Fear and Retaliationmentioning
confidence: 99%